2020
DOI: 10.1002/ajb2.1417
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability alters fitness trade‐offs: implications for evolution in stressful environments

Abstract: Premise Industrialization and human activities have elevated temperatures and caused novel precipitation patterns, altering soil moisture and nutrient availability. Predicting evolutionary responses to climate change requires information on the agents of selection that drive local adaptation and influence resource acquisition and allocation. Here, we examined the contribution of nutrient and drought stress to local adaptation, and we tested whether trade‐offs across fitness components constrain or facilitate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 91 publications
1
15
0
Order By: Relevance
“…Climate change has increased aridity in this system through reductions in snowpack and accelerations of snowmelt [ 41 , 50 , 58 ], which could exacerbate costs of reproduction at the lower end of the elevational gradient. Concordant with our results, drought stress imposed a strong growth cost of reproduction in B. stricta in a greenhouse experiment [ 59 ]. We suggest that these costs will become more apparent as climate change continues to augment drought stress in this landscape.…”
Section: Discussionsupporting
confidence: 91%
“…Climate change has increased aridity in this system through reductions in snowpack and accelerations of snowmelt [ 41 , 50 , 58 ], which could exacerbate costs of reproduction at the lower end of the elevational gradient. Concordant with our results, drought stress imposed a strong growth cost of reproduction in B. stricta in a greenhouse experiment [ 59 ]. We suggest that these costs will become more apparent as climate change continues to augment drought stress in this landscape.…”
Section: Discussionsupporting
confidence: 91%
“…Subsequent greenhouse experiments documented that trait divergence aligns with the niche models, such that water availability—and other selective pressures—likely underlie local adaptation (Lee and Mitchell‐Olds, 2013). A separate greenhouse manipulation of water and nutrient availability found that fitness declined with source elevation for Colorado accessions exposed to drought stress (MacTavish and Anderson, 2020), which is consistent with local adaptation of low‐elevation accessions to restricted water availability (Anderson and Wadgymar, 2020). Finally, a field study in five Colorado gardens revealed local adaptation to historical winter snowpack, again highlighting the importance of water in exerting selection on natural populations (Anderson and Wadgymar, 2020).…”
Section: Genus‐level Attributes Traits Of Primary Model Species Genus...mentioning
confidence: 54%
“…Phylogeographic data suggest that B. stricta likely recolonized high-elevation and highlatitude sites rapidly after the retreat of the Pleistocene glaciers (Song et al, 2006;Kiefer et al, 2009), suggesting that this species quickly responded to episodes of climate change in the geological past. Furthermore, manipulative experiments in the field, greenhouse, and growth chamber can expose diverse accessions to historical, contemporary, and future climatic conditions (Wadgymar et al, 2018a(Wadgymar et al, , 2018Bemmels and Anderson, 2019;Anderson and Wadgymar, 2020;MacTavish and Anderson, 2020). These studies evaluate how climate change could alter the adaptive landscape and whether populations could keep pace with novel conditions via plasticity or adaptation.…”
Section: Global Climate Changementioning
confidence: 99%
“…However, prioritizing reproduction at the cost of additional fat storage could increase the likelihood of mortality before the second breeding season or potentially limit future reproduction. Moreover, stressful or resource‐limited environments typically cause the highest costs for survival and reproduction and the strongest trade‐offs between life history traits (Boggs, 2009; MacTavish & Anderson, 2020; Stearns, 1989). Although males in our study had negligible fat stores, and fat and testes mass did not differ across temperature treatments, males may experience other reproductive costs of warming, including lower energy available for courtship, attractiveness of body size relative to other mates, and sperm quality.…”
Section: Discussionmentioning
confidence: 99%